Empresa Ciam Beef “Análisis De Mercado País Para Los Productos Cárnicos De La Empresa Ciam Beef - Suarez Pabon, Mishelle Alejandra (Universidad Antonio Nariño, 2023)
Determine Objectives of the internship the viability of exporting fine cuts of BEEF meat, from the factors of: logistic, operational and Administrative advice of the CIAM company; in order to identify potential markets in the 1.2.2 Specific objectives  abroad